2011
DOI: 10.1186/1471-2458-11-39
|View full text |Cite
|
Sign up to set email alerts
|

The intersection between sex and drugs: a cross-sectional study among the spouses of injection drug users in Chennai, India

Abstract: BackgroundIt is estimated that there are up to 1.1 million injection drug users (IDUs) in India; the majority are likely married. We characterize HIV, hepatitis B (HBV) and hepatitis C (HCV) prevalence and the risk environment of a sample of spouses of IDUs.MethodsA cohort of 1158 IDUs (99% male) was recruited in Chennai, India from 2005-06. A convenience sample of 400 spouses of the male IDUs in this cohort was recruited in 2009. A risk assessment questionnaire was administered and a blood sample collected. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…104 Sexual transmission of HCV has been shown to be infrequent (0.68%) in sexually transmitted disease clinics in Pune, Maharashtra. 105 Solomon et al 106 also found that heterosexual transmission of HCV is infrequent (0.5%).…”
Section: Sexual Transmissionmentioning
confidence: 97%
See 1 more Smart Citation
“…104 Sexual transmission of HCV has been shown to be infrequent (0.68%) in sexually transmitted disease clinics in Pune, Maharashtra. 105 Solomon et al 106 also found that heterosexual transmission of HCV is infrequent (0.5%).…”
Section: Sexual Transmissionmentioning
confidence: 97%
“…There is a need for large field studies to better understand HCV epidemiology and identify high-prevalence areas, and to identify and spread awareness about the modes of transmission of this infection in an attempt to prevent disease transmission. ( J CLIN EXP HEPATOL 2014;4: [106][107][108][109][110][111][112][113][114][115][116] understand the risk factors associated with transmission of this infection. This would also allow appropriate choice and targeting of efforts to prevent the spread of this disease, and thereby reduce the burden of chronic liver disease in the country.…”
mentioning
confidence: 99%
“…There are several cases on record where HCV infection could only be attributed to an HCV-infected sexual partner, as no other risk factor existed (Matthews et al, 2007). Most of this research was conducted in Europe, and to date there Evidence continues to accumulate in support of the sexual transmission of HCV (Solomon et al, 2011). There are several cases on record where HCV infection could only be attributed to an HCV-infected sexual partner (Matthews et al, 2007).…”
Section: Sexual Risk Factorsmentioning
confidence: 99%
“…Sexual behavior has been theorized to be associated with HCV infection as well (Solomon et al, 2011). There are several cases on record where HCV infection could only be attributed to an HCV-infected sexual partner, as no other risk factor existed (Matthews et al, 2007).…”
Section: Sexual Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation